Sharia beach as an alternative attraction for Islamic tourism in Indonesia - Nurhidayati, Sri Endah; Rashid, Basri (2019)
The authors present the type and packaging elements of the “sharia beach” at Santen Island in Banyuwangi. A qualitative approach, that is, a combination of post-positivism and constructivism paradigms, was adopted for the study. Data was collected from halal/sharia tourism business organizations, communities, religious leaders, and tourists. The results showed that the concept of sharia tourism in Santen Island would involve the development of tourist destinations with the guarantee of halal facilities, namely halal food, no alcohol vending, the notification time of worship (prayer), a holy place with facilities, as well as separation between men and women at relevant facilities. The result shall provide valuable information for industry players in terms of planning an Islamic tour package at this destination. In addition, this chapter shall enhance the body of knowledge particularly in relation to Islamic tourism literature.